Wolne Słowo . serwis informacyjny : pismo NSZZ "Solidarność" Regionu Toruńskiego, no. 74, 1981 - [NSZZ "Solidarność", [EIC Wiesław Cichoń] (NSZZ "Solidarność", 1981)
Creation and circulation: After introduction of the Martial Law, publication suspended in 1982-1988. Republished in 1989 as a weekly; For trade-union use